Recent Progress in Environmental Toxins-Induced Cardiotoxicity and Protective Potential of Natural Products - Yang, Yuanying; Wei, Shanshan; Zhang, Bikui; Li, Wenqun (Frontiers in Pharmacology, 2021)
Humans are unconsciously exposed to environmental toxins including heavy metals as well as various pesticides, which have deleterious effects on human health. Accumulating studies pointed out that exposure to environmental toxins was associated with various cardiopathologic effects. This review summarizes the main mechanisms of cardiotoxicity induced by environmental toxins (cadmium, arsenic and pesticides) and discusses the potential preventive effects of natural products. These findings will provide a theoretical basis and novel agents for the prevention and treatment of environmental toxins-induced cardiotoxicity. Furthermore, the limitations of current studies, future needs and priorities are discussed.